One hertz versus ten hertz repetitive TMS treatment of PTSD: A randomized clinical trial. (March 2019) - Kozel, F. Andrew; Van Trees, Kimberly; Larson, Valerie; Phillips, Sean; Hashimie, Jaffrey; Gadbois, Brian; Johnson, Suzanne; Gallinati, Jessica; Barrett, Blake; Toyinbo, Peter; Weisman, Mark; Centorino, Michael; et al.
Highlights: New treatments are critically needed to treat Posttraumatic Stress Disorder (PTSD). Whether high or low frequency right prefrontal rTMS is better for PTSD is unclear. Veterans with PTSD were randomized to right prefrontal 1 Hz rTMS versus 10 Hz rTMS. Both groups demonstrated significant improvement in PTSD and depression symptoms. No significant difference between groups on measures of PTSD, depression or function. Abstract: The purpose of this trial was to test whether right prefrontal cortex 1 Hz versus 10 Hz rTMS provides a significantly greater improvement in PTSD symptoms and/or function. Veterans 18 to 50 years of age suffering from PTSD were randomized to right prefrontal 1 Hz rTMS [2400 pulses/session] versus right prefrontal 10 Hz rTMS [2400 pulses/session]. The treatments were performed 5 days a week for 6 weeks with a 3-week taper using the NeuroStar system. There were one month and three months post treatment follow-up evaluations. Forty-four participants were enrolled with 17 being randomized to 1 Hz rTMS and 18 to 10 Hz rTMS. Both groups had significant improvement in PTSD and depression scores from baseline to the end of acute treatment. The 10 Hz group but not the 1 Hz group demonstrated significant improvement in function. Although both groups demonstrated significant improvement in PTSD and depression symptoms, a significant advantage for either the 1 Hz or 10 Hz frequency group on any of the scales acquired was not demonstrated. Further work is required with larger samples sizes to test whether low or high frequency is superior or if individual differences would indicate the more effective frequency.